Factor Input Prices and Unemployment in Uganda - Musiita, Benjamin; Kijjambu, Frederick Nsambu; Katarangi, Asaph Kaburura (Journal of Economics and Behavioral Studies, 2024)
Examining the impact of input costs on unemployment in Uganda, this study employed an ARDL model based on the Efficiency Wage Theory. Analyzing annual data from 1987 to 2019 and controlling for economic size and currency value, the research found that lending interest rates, real exchange rates, and GDP have a short-term negative impact on unemployment, suggesting an initial rise. However, the study highlights a positive long-run relationship between these factors and unemployment, indicating their potential to contribute to lower unemployment over time. Interestingly, no significant short-run or long-run effect of global crude oil prices on Uganda’s unemployment was identified. These findings suggest that while central bank policies promoting lower interest rates can encourage short-term investment and potentially lower unemployment, long-term economic growth is also crucial. Furthermore, the lack of impact from oil prices underscores the need for Ugandan policymakers to diversify the economy beyond oil dependence for sustainable unemployment reduction.